Synthesis and Characterization of Porous Materials from Waste Wheat Bran - İlknur Demıral; Canan Şamdan; Fatma Betül Kuş (Hittite Journal of Science and Engineering)

(untitled)
The purpose of this study was to investigate how the amount of ZnCl2 and temperature affect the process of converting waste wheat bran, known for its hemicellulose struc-ture, into porous material. The characterization of the wheat bran was done using proximate and primary component analysis, and Thermogravimetric analysis (TG) test, Fourier Transform Infrared Spectroscopy (FT-IR) spectra, Energy-dispersive X-ray spectroscopy (EDS) results, and Scanning electron microscopy (SEM) images. The influence of temperature on the surface areas of activated carbons is more significant than the impact of varying the amount of ZnCl2. When the carbonization temperature reached 500 °C, porous structures developed, and the highest surface areas achieved for all impregnation ratios (1:1, 2:1, and 3:1) were 1234, 1478, and 1422 m2/g, respectively. Activated carbon was found to have acidic (0.88 mmol/g) and basic (0.54 mmol/g) functional groups on its surface, after being synthesized through carbonization at 500 °C using ZnCl2 at a 2:1 impregnation ratio in accordance with Boehm titration. This promising activared carbon made from wheat bran, activated by ZnCl2, is efficient and environmentally friendly, and it is a potential solution for water pollution treatment.